Coincidence between malignant perivascular epithelioid cell tumor arising in the gastric serosa and lung adenocarcinoma - Yamada, Sohsuke (World J Gastroenterol, 2015)
A 4-mo history of both epigastralgia and back pain was presented in a 39-year-old male. Computed tomography showed right lung nodule and abdominal mass attached to the gastric wall, measuring approximately 30 mm and 70 mm in diameter. Since biopsy samples from the lung and abdomen revealed poorly differentiated adenocarcinoma and malignant tumor, clinicians first interpreted the abdominal mass as metastatic carcinoma, and a right lower lobectomy with following resection of the mass was performed. Gross examination of both lesions displayed gray-whitish to yellow-whitish cut surfaces with hemorrhagic and necrotic foci, and the mass attached to the serosa of the lesser curvature on the gastric body. On microscopic examination, the lung tumor was composed of a proliferation of highly atypical epithelial cells having abundant eosinophilic cytoplasm, predominantly arranged in an acinar or solid growth pattern with vessel permeation, while the abdominal tumor consisted of sheets or nests with markedly atypical epithelioid cells having pleomorphic nuclei and abundant eosinophilic to clear cytoplasm focally in a radial perivascular or infiltrative growth pattern. Immunohistochemically, the latter cells were positive for HMB45 or α-smooth muscle actin, but the former ones not. Therefore, we finally made a diagnosis of malignant perivascular epithelioid cell tumor (PEComa) arising in the gastric serosa, combined with primary lung adenocarcinoma. Furthermore, small papillary carcinoma of the thyroid gland was identified. The current case describes the coincidence of malignant PEComa with other carcinomas, posing a challenge in distinction from metastatic tumor disease.